Comparison of Sexual Dysfunction Using the Female Sexual Function Index following Surgical Treatments for Uterine Fibroids - Allison Ryann Louie; Jennifer Alice Armstrong; Laura Katherine Findeiss; Scott Craig Goodwin (Hindawi Limited, 2012)
Uterine fibroids are a common problem in women. Statistics showing 20-50% of fibroids produce symptoms and consequently patients seek surgical intervention to improve their quality of life. Treatments for fibroids are typically successful in controlling the fibroid disease, yet sexual function following invasive surgical treatments for fibroids can be jeopardized. The Sexual Function Index (FSFI) is a valid instrument producing quantifiable reproducible results. In this paper three case reports are evaluated by the FSFI and compared between the following treatment groups: hysterectomy, myomectomy, and uterine embolization. Our goal is to illustrate how each of these treatment outcomes can result in sexual dysfunction and therefore decreased quality of life. Effects of invasive fibroid treatments on sexual functioning would be helpful in guiding patient's ultimate decisions regarding treatment.